IN VITRO PROPAGATION OF CHINESE BAMBOO (Dracaena sanderiana L.) - Daquinta, Marcos (2010)
With the aim of to found a protocole to in vitro propagation of Chine bamboo (Draceana sanderiana L.), were evaluated different sterilizing time of bud with mercury biclorure (HgCl2) 0.2% (w/v), two culture condition (light and darkness) to the bud stablishment, different culture way and explants manegement to shoots proliferation and several IBA levelss to shoot rooting. The aclimatization was studied too. The in vitro stablishment of Dracaena sanderiana from lateral buds wase achieved in culture medium MS (1962) semi-solid suplement with 1 mg L-1 BAP under darkness. To shoot proliferation, the shoots longitudinal cut and permanent immersion systems in culture medium MS (1962) suplement with BAP (2 mg L-1) and ANA was the best tratament. The shoot aclimatization of Dracaena sanderiana was made in zeolita and sugarcane filter substrate (1:1) in green house condition with system by microjet.